(untitled) (Research, Society and Development, 2021)
O Access to medicines allows for the cure and treatment of various diseases, providing quality and increased life expectancy for users. However, the use of drugs can also cause undesirable effects and prevent the evolution of treatment, characterizing drug-related problems (DRPs), which develop during phases of the therapeutic process, such as prescription, dispensing and administration or resulting from the harmful process expected in the treatment. The purpose of this work is to demonstrate the importance of the pharmacist in detecting, preventing and solving problems resulting from pharmacotherapy. To support the elaboration, original articles were searched, in the databases, SciELO, Pubmed and LILACS. From the analysis of the studies, it is clear that the presence of errors in pharmacotherapy is quite frequent, in various audiences, compromising patient safety and causing even more damage, in addition to raising the costs of the system, so it is important to emphasize the importance of the pharmacist, acting in a preventive way to the emergence of DRPs, making interventions and drug reconciliation in order to reduce errors, interactions, adverse reactions and providing optimize pharmacotherapy.